Uterus Didelphys dengan Agenesis Servik Bilateral - Dwinda Rizary; Dedy Hendry (Andalas Obstetrics And Gynecology Journal, 2020)
Background : The mullerian duct anomaly is a congenital abnormality of the female reproductive system caused by abnormal embryological development during pregnancy. If accompanied by cervical agenesis and infertility, intervention must be taken. Accurate diagnosis and proper treatment are very crucial to the future of reproduction and treatment of infertility in patients.Objective: Reporting the handling of cases of uterine didelphys accompanied by bilateral cervical agenesis.Method : Case reportCase: Reported cases of women aged 34 years with primary amenorrhea and 9 years primary infertility, not typical cyclic pain, normal secondary sex development and from gynecological examination obtained cervical agenesis. Transvaginal ultrasound examination found a mass with the appearance of adenomyosis. Laparoscopic performed show 2 masses, 1 mass resembling adenomyosis with a size of 9x6x5cm located lateral to the left pelvis and another mass in the form of a hypoplastic uterus with a size of 2x2x1cm visible 2 tubes with 2 ovaries within normal limits. Uterine mass resembling adenomyosis with a location far from the vagina making it difficult to do anastomoses while other uterus hypoplasia and non-functional. Hysterectomies were performed on the mass of adenomyosis with the results of PA was adenomyosis.Conclusion: The uterus didelphys with bilateral cervical agenesis with 1 uterine adenomyosis and located in the pelvic lateral it was difficult to do uterovaginal anastomose so that hysterectomy was performed. Second uterine was hypoplasia and non-functional so that no action was taken. Need to think about "future fertility" in these patients and various options for having children. Keywords: Primary Amenorrhea, Uterine Didelphys, Cervical Agenesis, Adenomyosis